Polycyclic aromatic hydrocarbons in solid residue and volatile organic compounds in snow cover filtrate of Bratsk - Natalia Ivanovna Yanchenko; Larisa Ivanovna Belykh; Sergey Leonidovich Slutsky; Anna Viktorovna Lanko (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
Relevance of the study is determined by the need to obtain information on composition of gaseous and particulate air pollutants in the area of ??emission of the main industrial site of Bratsk, where there are large industrial enterprises, such as the production of primary aluminum and pulp and paper mill, thermal power plant, ferroalloy plant. The content of benzo (a) pyrene in aerosols in 2013 in the middle of the city exceeded the norm by three times. The malodorous substances in the surface layer of air reduce as well the quality of life of the population in Bratsk. During the last two or three years in the air of the Central area one can feeel new unpleasant smell, in addition to the familiar but unpleasant smell of sulfur compounds, originating from the pulp and paper industry. Object of the study is snow cover. Research methodology is the snow-chemical survey. Results. In December 2014 the authors selected the snow water filtrate, at the end of February 2015 they selected solid snow sediment samples. The polycyclic aromatic hydrocarbons were determined in snow solid sediment of Bratsk. The authors defined high correlation between the polycyclic aromatic hydrocarbons[h28] compounds in different parts of the emission area, as well as with polycyclic aromatic hydrocarbons[h29] of snow cover in the town with aluminum production - Novokuznetsk, and calculated the ratios for PAH of snow cover in Bratsk, Novokuznetsk and Shelekhov. The indicating ratios (fluoranthene/pyrene, fluoranthene) and (fluoranthene pyrene)/(chrysene+phenanthrene) display the pyrogenic nature of polycyclic aromatic hydrocarbon origin. For the first time the authors determined thirty-nine of volatile organic compounds in the filtrate of snow cover in Bratsk, including natural terpenoids. The coniferous forests or the pine needle processing can be a source of the latter.